Mainstreaming Parental Involvement in Post-Pandemic : Resolving Learning Loss with the Partnership Model in Elementary Schools - Widodo, Arif; Angga, Prayogi Dwina; Syazali, Muhammad; Umar, Umar (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This research aims to find best practices for using the partnership model to solve learning loss during a pandemic in elementary schools. The method of research was descriptive with a qualitative approach. Collecting data using interview techniques. The main instrument in this research was the researcher himself. The informants in the study were twenty-seven teachers from nine elementary schools in the districts of Central Lombok, West Lombok, and the City of Mataram. The research stages consist of data collection, condensation, presentation, and conclusion. Data analysis was carried out using data collection, reduction, presentation, and concluding techniques. The validity of the data was checked using dependency techniques. The study results showed that the partnership model used effectively reduces the post-pandemic learning loss phenomenon in elementary schools. The partnership model was implemented by optimizing parental involvement in learning and involving parents in evaluating learning outcomes.